A new species of Icerya Signoret (Hemiptera: Coccomorpha: Monophlebidae) and a key to species of the genus found in India - Joshi, Sunil; Navik, Omprakash; Veereshkumar, Veereshkumar (Zootaxa, 2021)
A new species of iceryine scale insect, Icerya viraktamathi Joshi sp. n. (Hemiptera: Monophlebidae), is described and illustrated based on adult females collected from Magnolia champaca (L.) Baill. ex Pierre (Magnoliaceae) in Meghalaya, North-East India. A taxonomic key to the species of Icerya Signoret known from India is provided. The new species appears to be related to I. zimmermanni, which is known from Indonesia, Thailand and India.